Upgrading Industri Rumahan Keripik Sukun Sebagai Inisiasi Kemandirian Ekonomi Masyarakat di Desa Tenggir Kecamatan Panji Kabupaten Situbondo - Saputra, Tri; Muhlison, Wildan; Rofiqi, Ahmad; Hani, Evita Soliha; Soeparjono, Sigit; Widuri, Laily Ilman; Yulianto, Roni; Alfarisy, Fariz Kustiawan (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Breadfruit chips are an example of post-harvest processing of breadfruit yields. Generally, breadfruit is only sold in the market in its raw form which has many drawbacks such as low selling price, and short shelf life, the fruit is easily damaged during the transportation process until rot occurs in the fruit. Processing breadfruit into breadfruit chips can help increase the profit margins you get. Breadfruit also has a certain harvest period or what is known as a seasonal plant can quickly experience decay so that post-harvest processing is deemed necessary to keep the product able to have a long shelf life. Tenggir Village, Panji District, Situbondo Regency is one of the villages with a relatively large number of breadfruit trees. Villagers already have the desire and enthusiasm to use the breadfruit by processing it into breadfruit chips. There is a need for community service to empower village potential and design solutions that will be offered to the community. The purpose of this program is to provide alternative solutions for simple postharvest processing of agricultural products and increase the production capacity of the breadfruit chips home industry. The result of implementing this program is an increase in one of the breadfruit chip processing home industries with indicators of increasing production capacity and business turnover. Greater support in science and finance could be scaled up to support more targeted and significant business development.